Redução da volatilização de amônia de dejetos líquidos suínos com mecanismos ácidos. - Pinto, Juliana de Souza (2023)
Pig farming has grown significantly in western Paraná, resulting in high production of waste, with great potential for environmental pollution if not treated correctly. The use of these wastes as a biofertilizer can be an interesting alternative for the agricultural sector by providing nutrients to plants, mainly nitrogen. Moreover, the application of biofertilizer can improve soil fertility by increasing organic matter, however, after nitrogen application in the soil, gaseous losses of this nutrient may occur, mainly in the form of ammonia. This process is called volatilization and can be intensified by different factors. Thus, the objective of this work was to evaluate the loss of nitrogen by volatilization after the application of manure with modified pH and the fertilization of corn with liquid pig manure with modified pH. The work was conducted in two experiments. Both were conducted in a greenhouse. In the first, the volatilization of ammonia was evaluated with the pH of liquid swine manure modified to 5.0 with four acids. In addition, two additional treatments were evaluated: manure with natural pH and the control (without manure application). To capture the volatilized ammonia, Sale-type collectors were used, with a static-free semi open chamber. The volatilization flow was analyzed; cumulative volatilization and percentage of ammonia loss. In the second, the corn crop was evaluated after the application of swine slurry with modified pH. On the day of sowing, 700 mL of manure were applied to the pots, the culture was irrigated daily. After 30 days of sowing, evaluations were performed. The height, chlorophyll content in the leaves, stem diameter and dry mass production of the aerial part of the plants were analyzed. The pH of pig manure changes the amount of volatilized ammonia. The application of pig manure with natural pH (7.19) resulted in ammonia losses of around 61.20%. With the acidification of the manure by adjusting the pH at 5.0 with ascorbic acid, N losses by volatilization reduced to 26%. The treatments with pH modified with ascorbic and sulfuric acid, presented lower ammonia volatilization index than the treatments with acetic and citric acid. Fertilization with swine slurry had a significant influence on plant height, chlorophyll, stem diameter and dry matter production of the aerial part of the plants. The acids used in the acidification of the DLS did not have a harmful effect on the parameters evaluated in the corn crop.